Baloncolí, deporte por la paz : un caballo de Troya a la violencia escolar (2010)
ABSTRACT: In the article the author of educational innovation has the potential baloncolí sports curriculum, teaching and learning of a proposal that is about to celebrate two decades (1993-2011) of existence. Hill was born at home Friend, rehabilitation institution for street girls run by the Capuchin Tertiary Sisters. Amid the daily assault of a group of women in special situations (drug addicts, street, etc.) Professor Amaya created a game that calls for the peaceful coexistence, respect and solidarity. This practice achieves installed in educational institutions in the municipality of Caldas and today is emerging as a sporting body and ludo proposed containment and resistance to the conflict that occurs in school.